Electrolytes Polymerization‐Induced Cathode‐Electrolyte‐Interphase for High Voltage Lithium‐Ion Batteries. Issue 39 (12th September 2021) - Yang, Jixiang; Liu, Xiang; Wang, Yian; Zhou, Xinwei; Weng, Lutao; Liu, Yuzi; Ren, Yang; Zhao, Chen; Dahbi, Mouad; Alami, Jones; Ei‐Hady, Deia Abd; Xu, Gui‐Liang; et al.
Abstract: Lithium‐ion batteries (LIBs) based on LiNix Coy Mn1‐x‐y O2 (NCM) cathode materials have been widely commercialized, because of their high energy density, favorable rate performance, and relatively low cost. However, with increased Ni content to further increase their energy density, their cycling stability deteriorates dramatically and thus fails to meet the commercial application requirements. The artificial cathode‐electrolyte‐interphase (CEI) is a promising approach to solve this problem. Here, a robust CEI is fabricated through in situ polymerization of ethylene carbonate induced by aluminum isopropoxide (AIP). By adding 1 wt.% AIP in a commercial electrolyte, the capacity retention of LiNi0.8 Co0.1 Mn0.1 O2 ||Li cell at 1 C rate has been significantly increased from 80.8% to 97.8% with a highly reversible capacity of 176 mA h g −1 after 200 cycles. AIP can be also used as an additive during the slurry‐making process, enabling a reversible capacity of 170 mA h g −1 for LiCoO2 after 200 cycles even at a high charge cut‐off voltage of 4.6 V. It is confirmed that the in situ formed CEI layer can prevent the cathodes from cracking and reduce the irreversible phase transformation. Abstract : An organic/inorganic cathode‐electrolyte interphase (CEI) is fabricated by in situ polymerization with Aluminum isopropoxide. Such a CEI layer can effectively prevent the layered cathode from cracking, irreversible phase transformation, and electrolyte decomposition. As a result, both LiCoO2 and LiNi0.8 Co0.1 Mn0.1 O2 cathodes exhibit a significantly improved cycling stability during harsh operation conditions such as high voltage and high‐temperature cycling.